Evaluation of lamb production potentiality of the Barind, Jamuna river basin and coastal region sheep of Bangladesh under intensive management (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study was conducted to investigate the lamb production potentiality in terms of nutrient intake and utilization, growth performances, carcass characteristics and meat quality of three regional native sheep under intensive management condition.Materials and methods: A total of 24 growing lambs having 08 lambs from each group with 4 to 6 months of age were used in this study. 40% urea molasses straw (UMS) and 60% concentrate mixture of the total diet were supplied according to lamb body weight. The total feed was offered at 4.0% live weight on dry matter basis of each animal. The completely randomized design was used in this experiment.Results: The dry matter intake was significantly (P